The antioxidants resveratrol and N-acetylcysteine enhance anthelmintic activity of praziquantel and artesunate against Schistosoma mansoni - Gouveia, Maria João (2020)
Free PMC article: https://www.ncbi.nlm.nih.gov/pmc/articles/pmid/31221193/